Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Menggunakan Model Discovery Learning Kelas IV SD - Wahyuni, Nindi Sri; Arwin, Arwin (Universitas Negeri Padang, 2021)
This study aims to describe the improvement of student learning outcomes in Integrated thematic Learning using Discovery Learning model in class IV SDN 05 Koto Tangah Kabupaten Agam. This research used a qualitative and quantitative approach. This type of research i.e. Research Action class (PTK). The subject of research is the grade IV SDN 05 Koto Tangah Kabupaten Agam Feed as many as 20 students. Research conducted two cycles. The design of the research include, (1) planning, (2) implementation, (3) and (4) observation of the reflection. The results showed an increase in: a) the RPP cycle I (C)77,77 % Cycle II (SB) 94,44% (SB) b) implementation on aspect of teacher cycle I82,81% (B), a cycle II 93,75% (SB) c) Implementation on aspect students cycle I 71,79,68 % (C) and Cycle II93,75 % (SB) d) student learning outcomes Cycle I 71,97 (B), cycle II 86,10 (A). Thus the model of Discovery Learning can improve the learning results of integrated thematic grade IV SDN 05 Koto Tangah Kabupaten Agam.